2005
DOI: 10.1146/annurev.biophys.34.040204.144452
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Sequence Motifs of Protein (Histone) Methylation Enzymes

Abstract: With genome sequencing nearing completion for the model organisms used in biomedical research, there is a rapidly growing appreciation that proteomics, the study of covalent modification to proteins, and transcriptional regulation will likely dominate the research headlines in the next decade. Protein methylation plays a central role in both of these fields, as several different residues (Arg, Lys, Gln) are methylated in cells and methylation plays a central role in the "histone code" that regulates chromatin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
334
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 320 publications
(341 citation statements)
references
References 126 publications
(165 reference statements)
6
334
0
1
Order By: Relevance
“…These peptides were subjected to enzymatic biotinylation, and peptide-bound biotin was probed using gel electrophoresis and streptavidin peroxidase. Both N [1][2][3][4][5][6][7][8][9] and N 7-14 were good targets for biotinylation by biotinidase but N [12][13][14][15][16][17][18][19][20] was not a good target (Fig. 1, lanes 1 -3).…”
Section: Biotinylation Sites In Histones H2a and H2axmentioning
confidence: 99%
See 2 more Smart Citations
“…These peptides were subjected to enzymatic biotinylation, and peptide-bound biotin was probed using gel electrophoresis and streptavidin peroxidase. Both N [1][2][3][4][5][6][7][8][9] and N 7-14 were good targets for biotinylation by biotinidase but N [12][13][14][15][16][17][18][19][20] was not a good target (Fig. 1, lanes 1 -3).…”
Section: Biotinylation Sites In Histones H2a and H2axmentioning
confidence: 99%
“…2, lane 1). If K9 was substituted with alanine (peptide K9A [1][2][3][4][5][6][7][8][9] ) no biotinylation was detectable (lane 2). In contrast, substitution of K5 with alanine residues (peptide K5A 1-9 ) did not decrease biotinylation (lane 3).…”
Section: Biotinylation Sites In Histones H2a and H2axmentioning
confidence: 99%
See 1 more Smart Citation
“…HKMTs can be classified according to the presence or absence and the nature of sequences surrounding the SET domain that are conserved within families [24,25]. Representatives of the major families include SUV, SET1, SET2, EZ, and RIZ (for example, see [26]). The SET7/9 and SET8 proteins do not fit into these families.…”
Section: Set Domain Proteinsmentioning
confidence: 99%
“…In human, mistargeting of hDOT1L to Hoxa9 (a leukemia-relevant gene) plays an important role in MLL (mixed lineage leukemia)-AF10-mediated leukemogenesish [73]. A sequence analysis [74] suggested that Dot1p possesses AdoMet-binding motifs characteristic of class-I MTases [75], similar to those in protein arginine MTases that modify arginines on many proteins including histones H3 and H4 [20,26]. Class-I MTases such as Dot1p are distinct from and do not contain the SET domain.…”
Section: Dot1p: Non-set Domain Hkmtmentioning
confidence: 99%